PENGARUH KUALIATAS PELAYANAN DAN LAYANAN TERHADAP LOYALITAS PENGUNJUNG HOTEL SARTIKA KUTACANE - maufira, Rila (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
Hotel Sartika Kutacane is a company in the field of hospitality services. To be able to continue to compete in the struggle for the Sartika Kutacane hotel market, always prioritize service quality as the spearhead to get new visitors as well as to maintain the loyalty of old visitors. The research method used in this study is descriptive analysis method with quantitative techniques. This research was conducted using the existing population and sampling technique. The sample in this study amounted to 83 respondents who are part of the overall visitors who stay at the Hotel Sartika Kutacane. The results showed that there was no positive and significant relationship between the independent variables (service quality) and (service quality) with the dependent variable (visitor loyalty) at the Hotel Sartika Kutacane. Based on the results of the t test, service quality has no effect on loyalty, it can be seen from the table that the significant value (0.369) is below (less than) 0.05 and t count (1.66 <0.903) if so, it can be interpreted that if the service quality variable is improved, it can be seen. that the value of Cronbach's alpha is 0.526, this means it is valid and can be used in research, it can be seen that the total correlation value is – 0.369, this means that the question failed to reject Ho. on visitor loyalty. This can be seen from the significant value (1.66 <0.05). Based on the validity test the value of the total correlation is 0.48, this means the question is valid and can be used in research. The results of multiple linear regression that examined the service quality variable did not have a positive and significant effect on visitor loyalty. This can be seen from the significant value (1.66 <0.05), then the results of the research are normal and the research is valid.